Pedestrians behaviour at unsignalized crosswalks: comparison of results based on simulated urban environments with field observations - Soares, Francisco Emanuel Cunha (2018)
[Excerpt] Introduction: Walking is the cleanest mode of transportation on earth, but the it is still one of the most dangerous. Knowing the pedestrians’ behavior in conflict zones is an essential step to reduce pedestrian crashes. The methods for this kind of analysis pass through sophisticated simulation methods, such as the virtual environments. This research is a part of the project AnPeB, the first approach done to the pedestrians’ behavior analysis on a pair of virtual urban environments recently developed, comparing the data collected through their implementation with field observations. [...]